Inward FDI and demand for skills in Sweden - Roger Bandick; Pär Hansson (Örebro University School of Business, 2005)
We observe a substantial increase of foreign ownership in Sweden in the 1990s. Did that have any effect on relative demand for skilled labor? Has technology transfers often associated with inward FDI led to increased demand for skills due to skilled-biased technical change? Are there any grounds for the worries in the public Swedish debate that more skilled activities have been moved abroad to countries where the headquarters are located? We obtain support for that the share of skilled labor tends to rise in non-multinationals but not in multinationals that become foreign owned. Yet it does not seem to be any relationship between increased foreign ownership and the relative demand for skilled labor in Swedish manufacturing between 1986 and 2000. Interestingly, increased competition from low-wage countries, rather than inward FDI, has had significant impact on skill upgrading, and appears to have played a larger role in the 1990s than before.
Keywords: F23; J23; J31; 330; foreign ownership; skill upgrading; wage differentials